Endometriosis in transgender men: recognizing the missing pieces - Vallée, Alexandre; Feki, Anis; Ayoubi, Jean-Marc (Frontiers in Medicine, 2023)
Endometriosis, traditionally associated with cisgender women, should be recognized as a significant issue for transgender men. This perspective highlights the need to address the unique experiences and challenges faced by transgender men with endometriosis. Diagnostic difficulties arise due to hormone therapy and surgical interventions, which can alter symptoms. Limited research in transgender men undergoing hysterectomy further complicates the understanding of endometriosis in this population. Healthcare providers must be aware of these challenges and adapt the diagnostic approaches accordingly. Education and inclusive care are essential to ensure timely and appropriate management of endometriosis in transgender men, ultimately improving their quality of life.